2016
DOI: 10.1037/met0000091
|View full text |Cite
|
Sign up to set email alerts
|

Gaining insights from social media language: Methodologies and challenges.

Abstract: Language data available through social media provide opportunities to study people at an unprecedented scale. However, little guidance is available to psychologists who want to enter this area of research. Drawing on tools and techniques developed in natural language processing, we first introduce psychologists to social media language research, identifying descriptive and predictive analyses that language data allow. Second, we describe how raw language data can be accessed and quantified for inclusion in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
241
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(245 citation statements)
references
References 109 publications
0
241
1
3
Order By: Relevance
“…We describe some relevant analyses related to LSA and the use of semantic representations. For a clear description of the methodology involved in performing text analyses based on LDA using large amounts of social media texts, see Kern et al (2016). All of the analyses described below may be carried out using www.semanticexcel.com (a user-friendly, online software solution; see Sikström, Kjell & Kjell, Appendix B).…”
Section: Using Semantic Representations In Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…We describe some relevant analyses related to LSA and the use of semantic representations. For a clear description of the methodology involved in performing text analyses based on LDA using large amounts of social media texts, see Kern et al (2016). All of the analyses described below may be carried out using www.semanticexcel.com (a user-friendly, online software solution; see Sikström, Kjell & Kjell, Appendix B).…”
Section: Using Semantic Representations In Analysesmentioning
confidence: 99%
“…For example, they found that the measures agreed with both self-reported as well as the informant's account of personality and that the measures were stable over a six-month period. Schwartz et al (2016) have also used texts from social media for predicting satisfaction with life. Lastly, Eichstaedt et al (2015) have used text from tweets in order to predict heart disease mortality on a county level, where they among other language features used LDA-derived topics.…”
Section: The Importance Of Big Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the frequent use of emotion language in status updates that relate to current experiences [13,14], for a large proportion of the population social media can provide unobtrusive access to time-sensitive and ecologically valid samples of expressed emotion [2,[41][42][43]. While observations of emotion variability and instability are yet to be applied to social media as a means of automatically screening for individuals at risk of depression, depression change has been demonstrated to be visible through changes in status update posting activity and content [2,4,10,44,45].…”
Section: Social Media and Emotion Dynamicsmentioning
confidence: 99%
“…dictionaries were supplemented by common emoji's and internet slang that indicated positive or negative emotion (see Multimedia Appendix 1). While not definitive, these inclusions were made to better reflect the language used on social media (for further discussion see [41]). …”
Section: Depression Symptom Severitymentioning
confidence: 99%